The effect of healthy lifestyle and psychological well-being on auditor performance moderating by auditor integrity - Fitriani, Rezki; Arifuddin, Arifuddin; Indrijawati, Aini (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to find out how the influence of healthy lifestyle and psychological well being on auditor performance is moderated by auditor integrity. The study used multiple regression analysis methods and moderation regression analysis. The population of this study is the auditors of the Inspectorate in South Sulawesi Province. Sampling of the respondents was carried out by purposive sampling. The results show that, healthy life style and psychological well-being have a positive and significant effort on auditor performance. The result also shows that, auditor integrity becomes a moderator between positive and significant effort healthy lifestyle on auditor performance, although on the other side can't be a moderator between psychological well-being on auditor performance.